Pengaruh Keadilan Distributif Kompensasi Dan Gaya Kepemimpinan Transformasional Terhadap Komitmen Afektif Karyawan Jne Banten Dengan Kepuasan Kerja Sebagai Variabel Intervening - Kurniatul Adawiyah; Heru Kurnianto Tjahjono; Fauziyah Fauziyah (Universitas Muhammadiyah Yogyakarta, 2016)
Each of the organizations concerned towards the best performance that produced by a series of systems that apply in these organizations. Human resource management is one of the key factors to get the best performance, because in addition to addressing the issue of expertise, skills and human resource management are also obliged to establish employee behavior conducive to getting the best performance. This research was conducted in Banten JNE to test four variables i.e. Justice distributif compensation, transformational leadership style as exogenous, job satisfaction as an intervening variable and affective commitment as an endogenous variable. Technique of data analysis in this study uses the SEM (Structural Equation Modeling). The respondents in this study as many as 130 employees comprising the whole permanent employees, contract and freelance. The results showed a positive effect compensation distributif justice significantly to job satisfaction, affective commitment and leadership style of influential positive significantly to job satisfaction however does not affect the commitment of the affective. Job satisfaction does not influential significantly to affective commitment.